8th North American Caribou Workshop, 20-24 April 1998, Whitehorse, Yukon, Canada. - Haugerud (ed. in chief), R.E.; Farnell (iss. eds.), R. (Rangifer, 2000)
Two hundred and forty people attended the 8th North American Caribou Workshop. Attendees brought perspectives from government and private sector research, management, industry, boards, councils and First Nations. As well, the involvement of colleagues from Norway, Finland, Greenland and Russia diversified these proceedings. Over 60 papers covering broad areas of caribou resource interests were given in both the plenary and poster sessions.